2021
DOI: 10.5194/tc-15-2415-2021
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of saline ice under cyclic flexural loading

Abstract: Abstract. New systematic experiments reveal that the flexural strength of saline S2 columnar-grained ice loaded normal to the columns can be increased upon cyclic loading by about a factor of 1.5. The experiments were conducted using reversed cyclic loading over ranges of frequencies from 0.1 to 0.6 Hz and at a temperature of −10 ∘C on saline ice of two salinities: 3.0 ± 0.9 and 5.9 ± 0.6 ‰. Acoustic emission hit rate during cycling increases with an increase in stress amplitude of cycling. Flexural strength o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Figure 4 also provides results obtained from experiments conducted on saline ice. In these experiments, before annealing, the saline ice was flexed at −10°C to outer‐fiber stress of 0.9 MPa for ∼300 cycles after gradually raising the stress amplitude, which raised the flexural strength to σfc ${\sigma }_{fc}$ = 1.4 ± 0.2 MPa from σf0= ${\sigma }_{f0}=$ 0.96 ± 0.13 MPa (Murdza et al., 2021). These experiments demonstrated that the cyclically‐induced flexural strength of saline ice is also fully relaxed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 also provides results obtained from experiments conducted on saline ice. In these experiments, before annealing, the saline ice was flexed at −10°C to outer‐fiber stress of 0.9 MPa for ∼300 cycles after gradually raising the stress amplitude, which raised the flexural strength to σfc ${\sigma }_{fc}$ = 1.4 ± 0.2 MPa from σf0= ${\sigma }_{f0}=$ 0.96 ± 0.13 MPa (Murdza et al., 2021). These experiments demonstrated that the cyclically‐induced flexural strength of saline ice is also fully relaxed.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of ice under cyclic loading and a corresponding decrease/increase in ice strength (more below) was investigated previously (D. M. Cole, 1990; Hammond et al., 2018; Haskell et al., 1996; Iliescu et al., 2017; Langhorne et al., 1998; Murdza et al., 2020, 2021). However, nothing (to our knowledge) has been reported on the evolution of the strength of ice during intervening “quiet” periods of low to no loading.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Murdza et al (2020b) showed that the flexural strength of freshwater S2 ice tested on the same loading system as used here compares well with direct measurements of the tensile strength of the same type of ice at the same conditions (Carter, 1971) when divided by 1.7. Murdza et al (2020aMurdza et al ( , 2021b showed that the flexural strength of lake Arctic ice tested under three-point bending is also similar to the one obtained in Murdza et al (2020b). By using this 1.7 factor to scale the values for saturated bond strengths shown in Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The ice density was 914.1 ± 1.6 kg m −3 (Golding et al, 2010); Young's modulus in the horizontal plane was 9.52 GPa (Snyder et al, 2016). Once grown, the ice was cut into blocks and stored in plastic cooler boxes in a cold room at −10 • C. Specimen preparation is described in detail elsewhere (Iliescu et al, 2017;Murdza et al, 2018Murdza et al, , 2019Murdza et al, , 2020bMurdza et al, , 2021a.…”
Section: Methodsmentioning
confidence: 99%